Suspended sediment transport in Rio Colorado agricultural basin, Argentina - Cancio, Nicolas C. O.; Pierini, Jorge O. (Frontiers in Built Environment, 2023)
The nutrient input from inland water discharges is vital for the development of marine aquatic fauna, being significantly sensitive to changes in water quality (WQ). The assessment of the contribution and distribution of some water quality parameters (e.g., nutrients, metals and inland organic compounds) is of vital importance, especially in irrigation basins. The study area is the Bonaerense Valley of the Colorado River (BVCR) and Mar Argentino, near the mouth of the Colorado River (Buenos Aires, Argentina). The study of water quality parameters is performed in an indirect way, by studying the spatiotemporal dynamics of cohesive sediment (CS), this is possible because the CS has a fundamental role in the transport of substances by adsorption/desorption interactions. We used numerical models (MOHID Land and MOHID Water) in a coupled way, evaluating the complex dynamics involved. The evaluated parameters (flow, velocity, cohesive sediment, salinity and temperature) were calibrated and subsequently validated with data from 7 monitoring stations, located along the Colorado River and adjacent water collectors. Calibration and validation values are within an acceptable range for the purposes, with mean values of 0.8 for NSE (Nash-Sutcliffe model efficiency coefficient), 0.9 (Pearson correlation) for calibration and 0.6 (NSE), 0.9 (Pearson) for validation. The irrigation zone (through the collectors) shows a significative contribution of cohesive sediment, on the order of 300 ppm. The river presents approximately 100 ppm and generates a plume along the coast to the northwest.